Analyses of structure phase stability of U-Mo target of the neutron source - Borts, B.V.; Laptev, I.N.; Parkhomenko, A.A.; Vanzha, A.F.; Vorobjev, I.A.; Marchenko, Yu.A. (Вопросы атомной науки и техники, 2020)
The paper presents analyses of structure phase stability of fuel materials by means of phase diagrams of martensite transformation method, proposed earlier for the system of “iron-carbon-vacancy”. It was shown that role of molybdenum in stabilization of uranium gamma-structure under irradiation is to hinder of the phase to phase transformations of martensite type. The role of point defects and electron structure in the process of homogenization of alloy structure in the process of irradiation was studied.